2011
DOI: 10.18357/ijcyfs23/420117757
|View full text |Cite
|
Sign up to set email alerts
|

“Single Mothers by Choice”: Disrupting Dominant Discourses of the Family Through Social Justice Alternatives

Abstract: This paper seeks to disrupt the dominant narrative of victimhood associated with the single mother family status. There are many barriers and difficulties associated with this status such as economic insecurity and political and social stigma. However, there are also many rewards and possibilities that make this family status desirable and rich with possibilities. Single mother families challenge the dominant paradigm of heteronormativity found within the notion of traditional nuclear family households. Drawin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…These single mothers who were working full-time had to count on support from domestic helpers, friends and/or extended family members for child-care (Martin & Alber, 2015). This corroborates the findings by Ajandi (2011), who revealed that single mothers' quest for independence contributed to elevating their self-efficacy and self-esteem. As Bourdieu (1976) postulated, the habitus of a person is incumbent on making positive life choices for improved access to education and enhanced human capital and this correlates with economic and social capital development.…”
Section: Positive Human Capital Developmentsupporting
confidence: 84%
See 2 more Smart Citations
“…These single mothers who were working full-time had to count on support from domestic helpers, friends and/or extended family members for child-care (Martin & Alber, 2015). This corroborates the findings by Ajandi (2011), who revealed that single mothers' quest for independence contributed to elevating their self-efficacy and self-esteem. As Bourdieu (1976) postulated, the habitus of a person is incumbent on making positive life choices for improved access to education and enhanced human capital and this correlates with economic and social capital development.…”
Section: Positive Human Capital Developmentsupporting
confidence: 84%
“…However, the limitation was that the menial income received from the state child support grant in South Africa placed severe restrictions upon single mothers who wanted to pursue post-secondary education (Raniga & Mathe, 2011). In this study the participants noted that post-secondary education was perceived by their line managers in their respective work sectors as a necessity and that their decision to pursue long-term education had improved their human capital development and upward mobility in the formal work sector (Ajandi, 2011). Hence it was not surprising to note from Table 1 that 20 (80%) of the women had secured well-paying jobs in either government, the private sector or higher education institutions.…”
Section: Positive Human Capital Developmentmentioning
confidence: 78%
See 1 more Smart Citation
“…Although many of the young women in this research come from abusive homes, their extended families or kinship networks are not a part of -and are often a refuge from -the abusive situations. Although commonly employed in the policy arena, narrow definitions of family that support a traditional and conservative view of family as consisting of those inside a nuclear family unit are hugely limiting, and fail to account for the wide range of personal connections that exist outside of that definition, be they extended biological families or families of choice (Quinless, 2013;Ajandi, 2011). Grandmothers, in particular, were often discussed as beloved and supportive, providing safe spaces for their grandchildren in times of need (McCaffrey, 2010;Sands, Goldberg-Glen, & Shin, 2009).…”
Section: Familiesmentioning
confidence: 99%
“…In addition, children who grow up without a father are problematic children. In order to change this perception and have healthy kids, single mothers need the protection of men (Ajandi 2011;Wiegers and Chunn, 2015;Smith 1997). The mothers who have been judged in every field throughout history are the ones who have kids without being married.…”
Section: Introductionmentioning
confidence: 99%